Accessibility and Connectivity Concept Between Motorcycles and Pedestrians at Education District. Issue 1 (May 2020) - Hidayat, B; Sari, N
Abstract: Land Transport Academy is one district of the education on Bekasi. Vehicle and pedestrian are the main traffic movement in the education district especially pedestrian and motorcycle. The condition of pedestrian facilities is not yet enough and not optimum, that be causing conflict between motorcycle and pedestrian. The conflict could to decrease level of road safety and to increase in road accident. Recently, the government has issued the Regulation of Safe and Safety Route for Schools (RASS) is focus for pedestrian safety at education district. This paper aims to propose the concept of accessibility and connectivity at education district, which could decrease road accident with develop safety routes for pedestrian. Basic concept of design was protected the pedestrian and decrease conflict between motorcycle and pedestrians. Research methodology includes observation of pedestrian and motorcycles movement, traffic counting, land use inventory of education district and pedestrian facilities. Data is analyzed by using qualitative description. The result is used to show separate pathway of pedestrians with traffic lane will be increasing of pedestrian safety. The separate pathway of pedestrians with traffic lane is to decrease conflict. The concepts of a school safety zone (Zoss) and pedestrian safety are very important for students in the education district.